(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2005)
Jurgen Habermas asserts that all knowledge is based upon human values. He criticises the values which underlie (positivistic) empirical science and instead suggests that hermeneutics provide a more appropriate basis for human sciences. However, Habermas rejects ordinary hermeneutics for its tendency to reify tradition and language, and to assume that subjects are aware of the meaning of their actions. Instead Habermas proposes a Critical Theory which has the eradication of unnecessary oppression and the maximization of human emancipation as its value. Habermas chooses Psychoanalysis as the model for this project. The following paper sketches this development from empiricism through hermeneutics to psychoanalysis. Although psychoanalysis can be viewed as a type of "depth hermeneutics" it also embodies many characteristics of an empirical science. It is suggested that this may make it inappropriate for Habermas’s task. However, the major problem is seen to be the power imbalance in the analytic situation, which leaves the analyst in charge of the interaction, interpretations, and possible emancipation of the patient. Also, it is suggested that the inadvertent consequence of analysis could be to adjust individuals to society rather than emancipate them. It is possible that psychoanalysis could be altered to empower the patient, and thereby be more consistent with the theory for which it is meant to be a model. Or perhaps other theories of intersubjective process and social critique would better fit Habermas’s intentions. One such alternative is briefly mentioned.